High-performance graded porous carbon aerogel catalyst as well as preparation method and application thereof
By preparing high-performance hierarchical porous carbon aerogel catalyst FeN-CA, the problem of high cost and poor performance of non-precious metal catalysts in fuel cells is solved, and the efficient electrochemical reaction in anion exchange membrane fuel cells is achieved. Zinc air battery and anion exchange membrane fuel cell.
Patent Information
- Application Number
- CN202411244562.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-07
AI Technical Summary
Existing non-precious metal catalysts have high cost and poor performance in anion exchange membrane fuel cells, requiring increased loading to rival precious metal catalysts, but resulting in incomplete exposure of active sites and low mass transfer efficiency.
Using high-performance graded porous carbon aerogel catalyst FeN-CA based on carbon aerogel, a trivalent iron atom doping ZIF-8 precursor with carboxymethyl cellulose was prepared by mixing the trivalent iron atom with carboxymethyl cellulose, lyophilized and carbonized. A catalyst with fractional pore size, multi-active sites and large specific surface area.
It achieves the improvement of the mass transfer capability of the catalyst while maintaining high activity, improves the efficiency and battery performance of the electrochemical reaction, and is suitable for zinc air batteries and anion exchange membrane fuel cells.
Smart Images

Figure CN119275303A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysts and relates to a high-performance hierarchical porous carbon aerogel catalyst and a preparation method and application thereof. Background Art
[0002] H 2 As a clean, high-energy-density energy source, it has become an ideal choice to replace fossil energy. Fuel cells are energy converters whose conversion efficiency is not limited by the Carnot cycle and can directly convert fuel (such as H 2 ) is converted into electrical energy. Among them, anion exchange membrane fuel cell (AEMFC) is an emerging fuel cell device. Because its working environment is alkaline, it is less corrosive and uses cheap bipolar plates. However, AEMFC still faces huge challenges in commercialization. One of the key challenges is that the cost of ORR catalyst accounts for a large proportion of the total battery cost. How to reduce the cost while achieving high activity and stability is a problem we must solve.
[0003] Currently, cheaper non-precious metal catalysts are used to replace expensive precious metal catalysts, which has become the main means to reduce the cost of ORR catalysts. However, for non-precious metal catalysts, the active site density needs to be increased to match the performance of precious metal catalysts such as Pt / C. This also leads to the load of non-precious metal catalysts increasing several times, resulting in problems such as incomplete exposure of active sites and inefficient mass transfer. Summary of the invention
[0004] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and propose a high-performance hierarchical porous carbon aerogel catalyst (FeN-CA) based on carbon aerogel, which has hierarchical pore size, multiple active sites, and a large specific surface area. While maintaining high activity, it also has excellent mass transfer capacity.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A method for preparing a high-performance hierarchical porous carbon aerogel catalyst comprises:
[0007] The ZIF-8 precursor Fe is doped with trivalent iron atoms in a mass ratio of (4-19):1. 3+ The / ZIF-8 solution and the carboxymethyl cellulose CMC solution are mixed and stirred and ultrasonicated to obtain a hydrogel, and the hydrogel is pre-frozen, freeze-dried and carbonized to obtain a high-performance hierarchical porous carbon aerogel catalyst FeN-CA.
[0008] Preferably, the carbonization temperature is 980-1400° C., the time is 30-600 min, and the heating rate is 2-7° C. / min.
[0009] More preferably, the carbonization temperature is 1050-1300° C., the time is 60-480 min, and the heating rate is 4-6° C. / min.
[0010] Preferably, the ZIF-8 precursor Fe is doped with trivalent iron atoms. 3+ Fe / ZIF-8 solution 3+ The preparation method of / ZIF-8 comprises: weighing ferric nitrate nonahydrate, zinc nitrate hexahydrate and dimethylimidazole in a mass ratio of (0.045-0.055):(0.85-0.87):1, dissolving the ferric nitrate nonahydrate and zinc nitrate hexahydrate in a methanol solution to obtain a solution A, and dissolving the dimethylimidazole in a methanol solution to obtain a solution B; mixing the solution A and the solution B, stirring and heating, and centrifuging and drying to obtain the solution.
[0011] Preferably, the ZIF-8 precursor Fe is doped with trivalent iron atoms. 3+ The solvent in the ZIF-8 solution is water and acetone in a volume ratio of (10-40):1.
[0012] Preferably, the method for preparing the high-performance hierarchical porous carbon aerogel catalyst comprises:
[0013] (1) Dissolve ferric nitrate nonahydrate and zinc nitrate hexahydrate in a methanol solution to obtain a solution A, and dissolve dimethyl imidazole in a methanol solution to obtain a solution B; mix the solution A and the solution B, stir, heat, and centrifuge to obtain Fe 3+ / ZIF-8;
[0014] (2) Weigh Fe 3+ / ZIF-8 precursor and carboxymethyl cellulose, doping trivalent iron atoms
[0015] The ZIF-8 precursor was added to the solvent and ultrasonically obtained solution C. Carboxymethyl cellulose CMC was dissolved in 60-90℃ water and stirred at room temperature to obtain solution D. Solution C and solution D were mixed and stirred by ultrasonication to obtain hydrogel Fe 3+ / ZIF-8@CMC;
[0016] (3) Hydrogel Fe 3+ / ZIF-8@CMC was pre-frozen at -25~-15℃ for 6~24h and then freeze-dried at -70~-90℃ to obtain aerogel Fe 3+ / ZIF-8@CMC-AG;
[0017] (4) Aerogel Fe 3+ / ZIF-8@CMC-AG was placed in a tubular furnace for carbonization to obtain a high-performance hierarchical porous carbon aerogel catalyst FeN-CA.
[0018] Preferably, the mass ratio of ferric nitrate nonahydrate, zinc nitrate hexahydrate and dimethylimidazole in (1) is (0.04-0.06):(0.7-0.9):1.
[0019] Preferably, the heating temperature in (1) is 50-70°C and the heating time is 100-140 min.
[0020] Preferably, Fe in (1) 3+ / The average particle size of ZIF-8 is 90~110nm.
[0021] Preferably, the solvent in solution C in (2) is water and acetone in a volume ratio of (10-40):1.
[0022] Preferably, the mass ratio of the trivalent iron atom-doped ZIF-8 precursor and carboxymethyl cellulose in (2) is (4-19):1.
[0023] More preferably, Fe 3+ The mass ratio of / ZIF-8 precursor and carboxymethyl cellulose is 14:1.
[0024] Preferably, the ultrasonication and stirring in (2) are both for 1 to 6 hours.
[0025] Preferably, in (3), the carbonization temperature is 980-1400°C, the time is 30-600 min, and the heating rate is 2-7°C / min.
[0026] More preferably, the carbonization temperature is 1050-1300° C., the time is 60-480 min, and the heating rate is 4-6° C. / min.
[0027] Preferably, the gas in the tubular furnace in (4) is an inert gas, including one or more of nitrogen and argon.
[0028] Preferably, the method for preparing the high-performance hierarchical porous carbon aerogel catalyst comprises:
[0029] (1) Weigh ferric nitrate nonahydrate, zinc nitrate hexahydrate, and dimethylimidazole in a mass ratio of (0.045-0.055):(0.85-0.87):1, dissolve the ferric nitrate nonahydrate and zinc nitrate hexahydrate in a methanol solution to obtain a solution A, and dissolve the dimethylimidazole in a methanol solution to obtain a solution B; mix the solution A and the solution B, stir, heat, and centrifuge to obtain a trivalent iron atom-doped ZIF-8 precursor Fe 3+ / ZIF-8;
[0030] (2) Weighing trivalent iron atom-doped ZIF-8 precursor and carboxymethyl cellulose in a mass ratio of (9-16):1 respectively, adding the trivalent iron atom-doped ZIF-8 precursor to a mixed solvent of water and acetone in a volume ratio of (10-40):1 by ultrasonication to obtain solution C, dissolving carboxymethyl cellulose CMC in water at 60-90°C, and stirring at room temperature to obtain solution D, and mixing solution C and solution D by ultrasonication to obtain hydrogel Fe 3+ / ZIF-8@CMC;
[0031] (3) Hydrogel Fe 3+ / ZIF-8@CMC was pre-frozen at -25~-4℃ for 6~24h and freeze-dried at -70~-90℃ for 24~72h to obtain aerogel Fe 3+ / ZIF-8@CMC-AG;
[0032] (4) Aerogel Fe 3+ / ZIF-8@CMC-AG was placed in a tubular furnace and carbonized at 1050-1300°C for 30-600 min to obtain a high-performance hierarchical porous carbon aerogel catalyst FeN-CA.
[0033] A high-performance hierarchical porous carbon aerogel catalyst, which has a concave dodecahedral hollow structure, an average particle size of 90-150nm, an average pore size of 6.1-7.2nm, and a specific surface area of 900-980m 2 g -1 .
[0034] Preferably, the high-performance hierarchical porous carbon aerogel catalyst has a mesoporous-microporous structure with a pore volume of 1.1 to 1.9 cm 3 / g, the volume ratio of mesopores to micropores is (2.1~3.8):1.
[0035] Preferably, the high performance hierarchical porous carbon aerogel catalyst has a mesoporous-microporous structure with a pore volume of 1.5 to 1.6 cm 3 / g, and the volume ratio of mesopores to micropores is 0.588:0.233.
[0036] Preferably, the high performance hierarchical porous carbon aerogel catalyst contains 2-3% nitrogen.
[0037] As a preferred option, Fe 3+ / ZIF-8 and CMC are cross-linked to form carbon aerogel.
[0038] An air cathode with a loading of 0.8 to 1.2 mg cm -2 High-performance hierarchical porous carbon aerogel catalyst.
[0039] Preferably, the preparation method of the air cathode comprises: dispersing a high-performance graded porous carbon aerogel catalyst and Nafion in an ethanol solution, ultrasonically obtaining a uniform slurry, dispersing the slurry on the surface of carbon paper, and assembling it with nickel foam to form an air cathode after drying at room temperature.
[0040] A zinc-air battery uses a zinc foil as an anode, an air cathode as a cathode, and a KOH aqueous solution as an electrolyte.
[0041] Preferably, the preparation method of the zinc-air battery comprises: assembling a polished zinc foil, an air cathode, and a 6MKOH aqueous solution into a zinc-air battery.
[0042] As a preferred embodiment, the power density of the zinc-air battery is 230-310 mW cm -2 .
[0043] A membrane electrode is composed of carbon paper, a cathode catalyst layer, an anode catalyst layer and an anion exchange membrane. The cathode catalyst layer is loaded with a high-performance graded porous carbon aerogel catalyst.
[0044] Preferably, the cathode catalyst layer is loaded with 1-3 mg cm -2 High-performance hierarchical porous carbon aerogel catalyst.
[0045] Preferably, the preparation method of the membrane electrode comprises: loading 1 to 3 mg cm -2 High-performance hierarchical porous carbon aerogel catalyst with a loading of 0.58-0.62 mg cm on the anode catalyst layer -2 The PtRu / C catalyst is then assembled into a membrane electrode using carbon paper, a cathode catalyst layer, an anode catalyst layer, and an anion exchange membrane.
[0046] Preferably, the method for preparing the membrane electrode comprises:
[0047] (1) dispersing FeN-CA and ionomer in a mass ratio of (0.8-0.6):(0.2-0.4) in a mixed solution of water and methanol to prepare a cathode catalyst slurry;
[0048] (2) dispersing a PtRu / C catalyst and an ionomer in a mass ratio of 9:1 in a mixed solution of water and methanol to prepare an anode catalyst slurry;
[0049] (3) By the CCM method, FeN-CA cathode catalyst slurry and PtRu / C anode catalyst slurry were sprayed on both sides of the anion exchange membrane respectively and heated and dried.
[0050] More preferably, the heating temperature is 60 to 90°C.
[0051] An anion exchange membrane fuel cell comprises a membrane electrode, a bipolar plate, a gasket and a current collecting plate.
[0052] Preferably, the preparation method of the anion exchange membrane fuel cell includes: soaking the membrane electrode in a 1M KOH aqueous solution for 1 to 2 hours and then washing it with ultrapure water, then sandwiching the membrane electrode assembly between gaskets and assembling it with a bipolar plate and a collector plate into an anion exchange membrane fuel cell.
[0053] Preferably, the power density of the anion exchange membrane fuel cell is 250 to 600 mW cm -2 .
[0054] More preferably, the anode of the anion exchange membrane fuel cell is loaded with 0.6 mg PtRu cm -2 ; cathode loading is 2 mg FeN-CA cm -2 The power density of the anion exchange membrane fuel cell reached 591 mW cm -2 .
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] 1. The present invention utilizes Fe 3+ / ZIF-8 plays a catalytic role, and CMC is used to construct hierarchical channels. After the two are mixed, they are freeze-dried and carbonized to obtain a high-performance hierarchical porous carbon aerogel catalyst with graded pore sizes, multiple active sites and large specific surface area.
[0057] 2. The present invention controls the heating rate, carbonization temperature and time during the carbonization process to ensure that the catalyst can maintain more pore structures and promote the generation of carbon nanotubes, thereby hopefully improving the efficiency of electron transfer and mass transfer in the battery and accelerating the efficient and fast electrochemical reaction. If the carbonization temperature is too high, the catalyst pores will collapse and the N content will decrease. If the layered pore structure cannot be formed, the active sites of the catalyst cannot be exposed more, the mass transfer is too slow, and the performance of the catalyst deteriorates, and the catalyst cannot exert its due activity and efficient mass transfer in the battery. If the temperature is too low, it is difficult to form active sites.
[0058] 3. The high-performance hierarchical porous carbon aerogel catalyst of the present invention is a concave dodecahedron hollow structure and has a carbon nanotube structure, which can accelerate mass and electron transport during electrochemical reactions.
[0059] 4. The high-performance hierarchical porous carbon aerogel catalyst of the present invention is applied to zinc-air batteries and anion exchange membrane fuel cells, has good electrochemical performance and wide applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 The aerogel Fe prepared in Example 1 of the present invention3+ Scanning electron microscope image of / ZIF-8@CMC-AG (50K).
[0061] Figure 2 This is a scanning electron microscope image (100K) of the high-performance hierarchical porous carbon aerogel catalyst prepared in Example 1 of the present invention.
[0062] Figure 3 This is a scanning electron microscope image (50K) of the high-performance hierarchical porous carbon aerogel catalyst prepared in Example 1 of the present invention.
[0063] Figure 4 This is a transmission electron micrograph of the high-performance hierarchical porous carbon aerogel catalyst prepared in Example 1 of the present invention.
[0064] Figure 5 This is a mapping diagram of the high-performance hierarchical porous carbon aerogel catalyst prepared in Example 1 of the present invention.
[0065] Figure 6 N is the high performance hierarchical porous carbon aerogel catalyst prepared in Example 1 of the present invention. 2 Adsorption-desorption curves.
[0066] Figure 7 This is a pore size distribution diagram of the high-performance hierarchical porous carbon aerogel catalyst prepared in Example 1 of the present invention.
[0067] Figure 8 This is a Raman graph of the high-performance hierarchical porous carbon aerogel catalyst prepared in Example 1 of the present invention.
[0068] Fig. 9 This is the LSV diagram of the high-performance hierarchical porous carbon aerogel catalyst prepared in Example 1 of the present invention.
[0069] Fig.10 This is a graph showing the methanol resistance of the high-performance hierarchical porous carbon aerogel catalyst prepared in Example 1 of the present invention.
[0070] Fig.11 This is a CV cycle stability diagram of the high-performance hierarchical porous carbon aerogel catalyst prepared in Example 1 of the present invention.
[0071] Fig.12 The polarization curve and power density diagram of the zinc-air battery prepared in Application Example 1 of the present invention.
[0072] Fig.13 The polarization curve and power density diagram of the anion exchange membrane fuel cell prepared in Application Example 5 of the present invention. DETAILED DESCRIPTION
[0073] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0074] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means.
[0075] Example 1
[0076] (1) 120 mg of ferric nitrate nonahydrate and 2.034 g of zinc nitrate hexahydrate were dissolved in 300 mL of methanol solution, which was recorded as solution A; 2.364 g of dimethylimidazole was dissolved in 300 mL of methanol solution, which was recorded as solution B. Both were stirred at 600 rpm for 15 min, and solution B was poured into solution A, heated and stirred at 60 °C for 60 min, and then centrifuged at 10000 rpm. The precipitate was collected and washed twice with 40 mL of methanol, and then dried at 70 °C for 12 h to obtain the trivalent iron atom-doped ZIF-8 precursor, which was recorded as Fe 3+ / ZIF-8.
[0077] (2) Weigh 650 mg of Fe 3+ / ZIF-8 was dissolved in a mixed solvent of water / acetone (v / v=20:1), and ultrasonicated for 3 h at room temperature to fully dissolve it, which was recorded as solution C; 46 mg of CMC was weighed and dissolved in 5 mL of water, and stirred at 400 rpm for 3 h to form a transparent hydrogel, which was recorded as solution D; solution C was poured into solution D, mixed and stirred for 3 h to mix well, and then ultrasonicated for 3 h to obtain hydrogel Fe 3+ / ZIF-8@CMC.
[0078] (3) Hydrogel Fe 3+ / ZIF-8@CMC was placed in a -19°C low-temperature refrigerator for 12 h, and then placed in a -80°C freezer for 48 h. The dried sample was recorded as Fe 3+ / ZIF-8@CMC-AG.
[0079] (4) Fe 3+ / ZIF-8@CMC-AG was fully ground and placed in a tubular furnace. Under a nitrogen atmosphere, the temperature was raised to 1100°C at a heating rate of 5°C / min, and carbonized at 1100°C for 120 min. The carbonized carbon was then cooled to room temperature to obtain a high-performance hierarchical porous carbon aerogel catalyst, which was recorded as 14:1FeN-CA.
[0080] Figure 1 The aerogel Fe in this embodiment 3+ / SEM image of ZIF-8@CMC-AG, Figures 2 to 4The scanning electron microscope image and the transmission electron microscope image of the high-performance hierarchical porous carbon aerogel catalyst in this embodiment show that the morphology of FeN-CA is a concave dodecahedral hollow structure and carbon nanotubes are generated; the average particle size is 100 nm.
[0081] Figure 5 This is the mapping diagram of FeN-CA. It can be seen that the C, N and Fe elements are evenly distributed.
[0082] Figure 6 , 7 N of FeN-CA 2 The adsorption-desorption curve and pore size distribution diagram show that the FeN-CA catalyst has a rich multi-level pore structure with an average pore size of 6.6 nm, a volume ratio of mesopores to micropores of 0.588:0.233, and a specific surface area of 927 m 2 g -1 .
[0083] Figure 8 This is the Raman graph of FeN-CA, which further proves that FeN-CA has a higher degree of graphitization.
[0084] Figures 9-11 They are the LSV diagram, methanol resistance diagram, and CV cycle stability diagram of FeN-CA, respectively. It can be seen that it has high ORR performance and stability.
[0085] Example 2
[0086] Compared with Example 1, the difference is that Fe 3+ The mass ratio of ZIF-8 and CMC is 19:1.
[0087] Example 3
[0088] Compared with Example 1, the difference is that Fe 3+ The mass ratio of ZIF-8 and CMC is 9:1.
[0089] Example 4
[0090] Compared with Example 1, the difference is that Fe 3+ The mass ratio of ZIF-8 and CMC is 4:1.
[0091] Application Example 1
[0092] The high-performance hierarchical porous carbon aerogel catalyst of Example 1 and Nafion were dispersed in an ethanol solution and ultrasonicated for 30 min to make the catalyst slurry reach a uniform dispersion state; a 2×2 cm 2 The carbon paper was washed with ethanol and then dried in an oven at 60°C. A certain amount of catalyst slurry was evenly dispersed on the carbon paper so that the catalyst mass loading reached 1 mg cm-2 , dried at room temperature; then it was combined with nickel foam to form an air cathode. A 0.2 mm polished zinc foil, air cathode, and 6 M KOH aqueous solution were assembled into a zinc-air battery.
[0093] Performance test. The maximum power density is 308mW cm -2 .
[0094] Application Example 2
[0095] Compared with Application Example 1, the difference is that the catalyst of Example 2 is prepared according to the method of Application Example 1 and the performance of the zinc-air battery is tested. The maximum power density is 235 mW cm -2 .
[0096] Application Example 3
[0097] Compared with Application Example 1, the difference is that the catalyst of Example 3 is prepared according to the method of Application Example 1 and the performance of the zinc-air battery is tested. The maximum power density is 250 mW cm -2 .
[0098] Application Example 4
[0099] Compared with Application Example 1, the difference is that the catalyst of Example 4 is prepared according to the method of Application Example 1 and the performance of the zinc-air battery is tested. The maximum power density is 270 mW cm -2 .
[0100] Fig.12 The polarization curve and power density diagram of the zinc-air battery in this application example show that the maximum power density is 308 mW cm -2 .
[0101] Application Example 5
[0102] The high performance hierarchical porous carbon aerogel catalyst of Example 1 is used as a cathode catalyst in an anion exchange membrane fuel cell.
[0103] FeN-CA and ionomer with a mass ratio of 8:2 were dispersed in a mixed solution of water and methanol (m / m=3:4) to prepare cathode catalyst slurry; PtRu / C catalyst and ionomer with a mass ratio of 9:1 were dispersed in a mixed solution of water and methanol (m / m=3:4) to prepare anode catalyst slurry; FeN-CA cathode catalyst slurry and PtRu / C anode catalyst slurry were sprayed on both sides of the anion exchange membrane, heated and dried at 80°C to obtain membrane electrode. The anode catalyst loading is 0.6mg PtRucm -2 ; The cathode catalyst loading is 2 mg FeN-CA cm -2 .
[0104] The membrane electrode was soaked in 1M KOH aqueous solution for 2 hours, and then the excess KOH on the membrane electrode surface was washed with ultrapure water. Subsequently, the membrane electrode was clamped between the gaskets and assembled with the bipolar plate and the collector plate into an anion exchange membrane fuel cell using a torque wrench. Test H 2 -O 2 Performance of AEMFC, cell temperature and humidified H 2 and O 2 The gas temperature is 80℃, H 2 and O 2 The flow rate is 0.5L min -1 The maximum power density obtained from the test is 317mW cm -2 .
[0105] Application Example 6
[0106] Compared with Application Example 5, the difference is that the mass ratio of FeN-CA to ionomer is 6:4. Test H 2 -O 2 The performance of AEMFC is tested with a maximum power density of 370 mW cm -2 .
[0107] Application Example 7
[0108] Compared with Application Example 5, the difference is that the cathode loading is 1 mg FeN-CA cm -2 . Assemble the battery and test H 2 -O 2 The performance of AEMFC. The maximum power density obtained by testing is 256mW cm -2 .
[0109] Application Example 8
[0110] Compared with Application Example 5, the difference is that the cathode loading is 2 mg FeN-CA cm -2 . Assemble the battery and test H 2 -O 2 The performance of AEMFC. The maximum power density obtained by testing is 591mW cm -2 .
[0111] Application Example 9
[0112] Compared with Application Example 5, the difference is that the cathode loading is 3 mg FeN-CA cm -2 . Assemble the battery and test H 2 -O 2 The performance of AEMFC. The maximum power density obtained by testing is 359mW cm -2 .
[0113] Fig.13 The polarization curve and power density diagram of the anion exchange membrane fuel cell in this application example show that the maximum power density is 591 mW cm -2 .
[0114] In this paper, within a certain range, as Fe 3+ With the increase of the mass ratio of ZIF-8 to CMC, the maximum power density of the prepared zinc-air battery first increases and then decreases.
[0115] In this paper, within a certain range, in anion exchange membrane fuel cells, with the increase of the loading amount of high-performance hierarchical porous carbon aerogel catalyst FeN-CA in the cathode, the maximum power density first increases and then decreases.
[0116] In summary, the present invention utilizes Fe 3+ / ZIF-8 plays a catalytic role, and CMC is used to construct hierarchical pores. After the two are mixed, they are freeze-dried and carbonized to obtain a high-performance hierarchical porous carbon aerogel catalyst with graded pore size, multiple active sites and large specific surface area. The high-performance hierarchical porous carbon aerogel catalyst is used in zinc-air batteries and anion exchange membrane fuel cells, has good electrochemical properties and is widely applicable.
[0117] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A method for preparing a high-performance hierarchical porous carbon aerogel catalyst, characterized in that: The preparation method comprises: doping a ZIF-8 precursor Fe with trivalent iron atoms at a mass ratio of (4-19):1 3+ The / ZIF-8 solution and the carboxymethyl cellulose solution are mixed and stirred and ultrasonicated to obtain a hydrogel, and the hydrogel is pre-frozen, freeze-dried and carbonized to obtain a high-performance hierarchical porous carbon aerogel catalyst FeN-CA.
2. The method for preparing a high-performance hierarchical porous carbon aerogel catalyst according to claim 1, characterized in that: The trivalent iron atom doped ZIF-8 precursor Fe 3+ Fe / ZIF-8 solution 3+ The preparation method of / ZIF-8 comprises: weighing ferric nitrate nonahydrate, zinc nitrate hexahydrate, and dimethylimidazole in a mass ratio of (0.045-0.055):(0.85-0.87):1, dissolving the ferric nitrate nonahydrate and zinc nitrate hexahydrate in a methanol solution to obtain a solution A, and dissolving the dimethylimidazole in a methanol solution to obtain a solution B; mixing the solution A and the solution B, stirring and heating, and centrifuging and drying to obtain; The trivalent iron atom doped ZIF-8 precursor Fe 3+ The solvent in the ZIF-8 solution is water and acetone in a volume ratio of (10-40):
1.
3. The method for preparing a high-performance hierarchical porous carbon aerogel catalyst according to claim 1, characterized in that: The carbonization temperature is 980-1400° C., the time is 30-600 min, and the heating rate is 2-7° C. / min.
4. The method for preparing a high-performance hierarchical porous carbon aerogel catalyst according to claim 1, characterized in that: The preparation method comprises: (1) Dissolve ferric nitrate nonahydrate and zinc nitrate hexahydrate in a methanol solution to obtain a solution A, and dissolve dimethyl imidazole in a methanol solution to obtain a solution B; mix the solution A and the solution B, stir, heat, and centrifuge to obtain Fe 3+ / ZIF-8; (2) Weigh Fe 3+ / ZIF-8 precursor and carboxymethyl cellulose, add the trivalent iron atom doped ZIF-8 precursor to the solvent and ultrasonically obtain solution C, dissolve carboxymethyl cellulose CMC in 60-90℃ water, and then stir at room temperature to obtain solution D, mix solution C and solution D, stir and ultrasonically obtain hydrogel Fe 3+ / ZIF-8@CMC; the solvent in the solution C is water and acetone in a volume ratio of (10-40):1; (3) Hydrogel Fe 3+ / ZIF-8@CMC was pre-frozen at -25~-15℃ for 6~24h and then freeze-dried at -70~-90℃ to obtain aerogel Fe 3+ / ZIF-8@CMC-AG; (4) Aerogel Fe 3+ / ZIF-8@CMC-AG was placed in a tubular furnace for carbonization to obtain a high-performance hierarchical porous carbon aerogel catalyst FeN-CA.
5. A high-performance hierarchical porous carbon aerogel catalyst prepared by the method for preparing a high-performance hierarchical porous carbon aerogel catalyst according to any one of claims 1 to 4, characterized in that: The high-performance hierarchical porous carbon aerogel catalyst has a concave dodecahedral hollow structure, an average particle size of 90 to 200 nm, an average pore size of 6.1 to 7.2 nm, and a specific surface area of 900 to 980 m 2 g -1 .
6. The high-performance hierarchical porous carbon aerogel catalyst prepared by the method for preparing a high-performance hierarchical porous carbon aerogel catalyst according to claim 5, characterized in that: The high-performance hierarchical porous carbon aerogel catalyst has a mesoporous-microporous structure with a pore volume of 1.1 to 1.9 cm 3 / g, the volume ratio of mesopores to micropores is (2.1~3.8):
1.
7. An air cathode, characterized in that: Its loading is 0.8~1.2mg cm -2 The high-performance hierarchical porous carbon aerogel catalyst prepared by the method for preparing a high-performance hierarchical porous carbon aerogel catalyst as described in any one of claims 1 to 4, and / or the high-performance hierarchical porous carbon aerogel catalyst as described in any one of claims 5 to 6.
8. A zinc-air battery, characterized in that: The zinc foil is used as the anode, the air cathode as claimed in claim 7 is used as the cathode, and the KOH aqueous solution is used as the electrolyte.
9. A membrane electrode, characterized in that: It consists of carbon paper, a cathode catalyst layer, an anode catalyst layer, and an anion exchange membrane. The cathode catalyst layer is loaded with a high-performance hierarchical porous carbon aerogel catalyst prepared by the preparation method of a high-performance hierarchical porous carbon aerogel catalyst as described in any one of claims 1 to 4, and / or a high-performance hierarchical porous carbon aerogel catalyst as described in any one of claims 5 to 6.
10. An anion exchange membrane fuel cell, characterized in that: It comprises the membrane electrode, bipolar plate, gasket and collector plate as claimed in claim 9.
Citation Information
Cited By
Proton exchange membrane electrode, preparation method thereof and proton exchange membrane fuel cell
CN121726422A